ANALISIS RASIO LIKUIDITAS DAN RASIO RENTABILITAS PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK DAN PT. BANK NEGARA INDONESIA (PERSERO) TBK DARI TAHUN 2014 – 2018 - Dheri Febiyani Lestari; Yudi Setia Rachmanda (LP2M Universitas Perjuangan Tasikmalaya, 2022)
The purpose of this research is to know the financial performance and financial performance comparison between PT. Bank Rakyat Indonesia, Tbk and PT. Bank Negara Indonesia, Tbk for five years when viewed from the financial ratios of liquidity and profitability. The object of this research is Bank Rakyat Indonesia and Bank Negara Indonesia in 2014-2018. The method used in this study is a qualitative descriptive analysis with the research subjects of financial report data during the 2014-2018 period. The research uses data collection techniques in the form of document studies. The liquidity ratio is measured by 3 ratios, namely the current ratio, quick ratio and cash ratio. While the profitability ratio is measured by 2 ratios, namely Return On Assets and Return On Equity. The results of the research on liquidity ratios at Bank BRI show unhealthy results, while the quick ratio and cash ratio data have fairly healthy data. BNI has an unhealthy current ratio, quick ratio and unhealthy cash ratio. Meanwhile, the profitability ratios have very healthy and unhealthy data in common. Healthy data are shown in ROA and ROE while unhealthy data are shown in BOPO and NPM. Keywords: Financial Performance, Liquidity Ratio and Profitability Rasio